Is aortic valve-sparing root reimplantation (David-I) justified in cardiac redo surgery?. (24th March 2022) - Beckmann, Erik; Kaufeld, Tim; Martens, Andreas; Rudolph, Linda; Krüger, Heike; Natanov, Ruslan; Haverich, Axel; Shrestha, Malakh Lal
Abstract: OBJECTIVES: Aortic valve-sparing root reimplantation (AVSRR) is a complex procedure, which offers the benefit of preserving the native aortic valve. Cardiac redo surgery is complex and time-consuming, and it is not known if David procedure is safe or beneficial in this context. METHODS: Between 1993 and 2019, we performed a total of 544 elective AVSRR operations at our centre. Patients were assigned to either group A ( n = 30, redo) or group B ( n = 514, first-time sternotomy). RESULTS: Aortic cross-clamp time was higher in the redo group (173[62] vs 125[31], P < 0.001). Cardiopulmonary bypass time was higher in the redo group as well (250[78] vs 179[51], P < 0.001). There were significantly more concomitant total arch replacements in the redo group (43.3% vs 5.8%, P < 0.001) using the 'beating heart' technique (20.0% vs 1.9%, P < 0.001). In-hospital mortality was comparable in both groups (3.3% vs 1.8%, P = 0.44). The rates for perioperative complications in terms of permanent neurological deficit and rethoracotomy were comparable between the 2 groups, too. Follow-up was complete for 99.6% of all patients and comprised a total of 584 patient-years. The 1-, 5-, 10- and 15-year survival rates were 90%, 81%, 60% and 55%, in group A (redo) and 96%, 90%, 78% and 67% in group B (native, P = 0.16), respectively. The rates for freedom from valve-related reoperation at 1, 5, 10 and 15 years after initial surgery were 96%, 92%, 92% and 92% in group A (redo) and 97%, 92%, 87% and 84% in group B (native, P = 0.52), respectively. CONCLUSIONS: Despite significantly more concomitant total arch replacements in the redo group, early mortality was comparable in both groups. We conclude that AVSRR can be performed in redo cardiac surgery without compromising the early postoperative outcome. Careful patient assessment and selection are mandatory when evaluating patients with a history of previous cardiac surgery for David procedure. Abstract : Aortic valve-sparing root reimplantation (AVSRR) has been introduced in 1992 [1].